Tp-e interval, Tp-e/QT and Tp-e/QTc ratio in hypertensive patients with primary aldosteronism. (2nd January 2020) - Demirtas, Derya; Sumbul, Hilmi Erdem; Bulut, Atilla; Demirtas, Abdullah Orhan; Gulumsek, Erdinc; Koca, Hasan; Icen, Yahya Kemal; Koc, Mevlut
ABSTRACT: Introduction : There is no study evaluating the Tp-e/QT and Tp-e/QTc ratios with T wave peak to end interval (Tp-e interval) used for evaluation of cardiac arrhythmia risk and ventricular repolarization changes in patients with primary aldosteronism (PA). We aimed to investigate whether there was a change in Tp-e interval, Tp-e/QT and Tp-e/QTc ratios in patients with PA. Method : Thirty patients with newly diagnosed hypertension (HT) and PA and 30 patients with primary HT were included. Twelve-lead electrocardiography (ECG) was performed in all patients. Tp-e interval, Tp-e/QT and Tp-e/QTc ratios were measured in addition to routine measurements in ECG. Results : Sodium, potassium, and plasma renin activity (PRA) were significantly lower in patients with PA; systolic and diastolic blood pressure, plasma aldosterone, plasma aldosterone/PRA were significantly higher in patients with PA ( p < .05 for each one). When ventricular repolarization parameters were examined; while QT and QTc interval were similar between two groups, Tp-e interval, Tp-e/QT and Tp-e/QTc ratio values were significantly higher in patients with PA ( p < .05 for each one). Tp-e interval, Tp-e/QT and Tp-e/QTc ratio values were positively correlated with the serum calcium, aldosterone, and aldosterone/PRA levels and negatively correlated with serum sodium, potassium, renin levels ( p < .05 for each one). In linear regression analyses, Tp-e interval, Tp-e/QT and Tp-e/QTc ratios were independently associated with the aldosterone/PRA ratio. Conclusion : Tp-e interval, Tp-e/QT and Tp-e/QTc were increased in hypertensive patients with PA and were independently associated with aldosterone/PRA levels. This may be related to the changing neuroendocrine state in patients with PA.